2018
DOI: 10.3390/md16120509
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral and Antioxidant Properties of Echinochrome A

Abstract: The aim of this study was to examine the in vitro antioxidant and antiviral activities of echinochrome A and echinochrome-based antioxidant composition against tick-borne encephalitis virus (TBEV) and herpes simplex virus type 1 (HSV-1). The antioxidant composition, which is a mixture of echinochrome A, ascorbic acid, and α-tocopherol (5:5:1), showed higher antioxidant and antiviral effects than echinochrome A. We suppose that echinochrome A and its composition can both directly affect virus particles and indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 31 publications
1
55
0
1
Order By: Relevance
“…Thus, thousands of compounds from various marine organisms such as algae, bacteria, fungi, marine invertebrates or sponges have been screened and 21 of them have demonstrated antiviral activities [17]. In 2018, Fedoreyev et al [2] reported that an antioxidant "soup", containing echinochrome A (pigment of sea urchins), ascorbic acid (vitamin C) and α-Tocopherol (vitamin E) possess in vitro antiviral activity against RNA-containing tick-borne encephalitis virus and DNA-containing herpes simplex virus type 1 [2]. This study also demonstrated that a synergistic effect of antioxidant molecules can be effective against virus infections.…”
Section: Marine Antioxidants and Antiviral Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, thousands of compounds from various marine organisms such as algae, bacteria, fungi, marine invertebrates or sponges have been screened and 21 of them have demonstrated antiviral activities [17]. In 2018, Fedoreyev et al [2] reported that an antioxidant "soup", containing echinochrome A (pigment of sea urchins), ascorbic acid (vitamin C) and α-Tocopherol (vitamin E) possess in vitro antiviral activity against RNA-containing tick-borne encephalitis virus and DNA-containing herpes simplex virus type 1 [2]. This study also demonstrated that a synergistic effect of antioxidant molecules can be effective against virus infections.…”
Section: Marine Antioxidants and Antiviral Activitymentioning
confidence: 99%
“…Oxidative stress-a loss in the balance between the production of free radicals including reactive oxygen species (ROS) and antioxidant cell signaling pathways [2]-can be a key factor of the pathogenesis in many acute or chronical human diseases [3]. Dietary intake of exogenous antioxidants in humans has a well-known role in preventing and protecting cellular oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…9 It was established that the sea urchin pigment echinochrome (1) and its mixtures with other antioxidants directly affect the HSV-1 virus particles and improve the antioxidant defense mechanisms in the infected cells. 10 These results demonstrate that echinochrome 1 and related natural hydroxy 1,4-naphthoquinones 2 to 5 (Figure 1) are the promising starting compounds for the development of new antiviral drugs.…”
mentioning
confidence: 81%
“…By contrast, Acyclovir demonstrated only minor virucidal effect (IC 50 >200) against HSV-1, as noted by other researchers. 10,26,27 We can assume that the mechanisms of action of thioglucoside 17 are the direct inactivation of virus particles and partially the inhibition of virus attachment and virus binding. It is well known that natural polyphenols are targeted to the HSV-1 glycoproteins, The results are given as mean ± standard deviation (n = 3).…”
Section: Cytotoxicity and Antiviral Activity Of Compoundsmentioning
confidence: 99%
“…Somov Institute of Epidemiology and Microbiology (Vladivostok), and Institute of Vaccines and Sera (Moscow) has found that Ech A not only exhibits anti-oxidant properties, but also shows anti-viral activities against tick-borne encephalitis virus and herpes simplex virus type 1. A mixture of Ech A, ascorbic acid and tocopherol (5:5:1) showed even higher anti-oxidant and anti-viral effects in comparison with Ech A itself [13].…”
Section: Ofmentioning
confidence: 93%